PENGARUH KEPEMIMPINAN SITUASIONAL DAN BUDAYA ORGANISASI TERHADAP KOMITMEN GURU DI MADRASAH TSANAWIYAH NEGERI KOTA TANJUNGBALAI - Nasution, Rizlan (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to analyze (1) To analyze the influence of situational leadership on teacher commitment in Madrasah Tsanawiyah State of Tanjungbalai City. (2) To analyze the influence of organizational culture on the commitment of teachers in Madrasah Tsanawiyah State of Tanjungbalai City. (3) To analyze the influence of situational leadership and organizational culture together on the commitment of teachers in Madrasah Tsanawiyah State of Tanjungbalai City.The type of research used is quantitative research with questionnaire dissemination methods. Sampled in this study 51 teachers in Madrasah Tsanawiyah State of Tanjungbalai City. The calculation of analytical tests in this study was conducted using the Statistical Package for Social Science (SPSS) program.Based on the results of research that (1) situational leadership has a significant effect on the commitment of teachers in Madrasah Tsanawiyah State of Tanjungbalai City. This is characterized by the value given X1 (situational leadership) to Y (teacher commitment) of 31,2% and positive means that the greater the situational leadership of the principal of Madrasah Tsanawiyah State of Tanjungbalai (X1) the greater the teacher commitment (Y). tcount at X1 = 2.394 >ttable (0.05;49) = 0.2329 or by comparing sig value = 0.001 < error level of 5% = 0.05.(2) The culture of significant influential organizations has a teacher commitment in Madrasah Tsanawiyah State of Tanjungbalai City. This is characterized by an X2 (organizational culture) value to Y (teacher commitment) of 31,4% and positive means that the greater the organizational culture (X2) the greater the teacher commitment (Y). tcount at X2 = 2,413 >ttable (0.05;49) = 0.2329 or by comparing the value of sig = 0.000 < error level of 5% = 0.05.(3) Situational leadership variables and organizational culture had an effect of 50,10% on teacher commitment in Madrasah Tsanawiyah State of Tanjungbalai City. Simultaneously situational leadership and organizational culture are low to the commitment of teachers in Madrasah Tsanawiyah State of Tanjungbalai City